High-order Supper-twisting Based Terminal Sliding Mode Control Applied on Three Phases Permanent Synchronous Machine - Karboua, Djaloul; Toual, Belgacem; Kouzou, Abdellah; Douara, Ben Ouadeh; Mebkhouta, Toufik; Bendenidina, Ali Nacreddine (Periodica polytechnica. Electrical engineering and computer science, 2023)
Nowadays, research on electric drive control has become popular because hybrid methods to collect the advantages of individual controllers. Moreover, these methods aim to reach better performance and robust control even in the presence of uncertainties and disturbances which are typically evident in high-speed dynamics where the influence of external disturbances and modeling errors are more evident. Therefore, in this paper, a novel hybrid controller is proposed between the super-twisting algorithm based on high order design (HO-STA) and terminal sliding mode control (T-SMC) applied on a permanent magnet synchronous motor PMSM. Whereas, it accounts to deal with the weaknesses of both terminal sliding mode control and super twisting algorithm (STA) and at the same time combining their advantages; furthermore, it provides exceptional characteristics, including fast finite-time convergence, stabilization of the performance and its reaching law developer based on new design which contributes to reducing the chattering problems afflicted by C-SMC. This proposed hybrid technique contributes to gaining robust control under variation between slow, medium, and high speed levels, no matter what load torque is applied or whatever PMSM parameters change. Moreover, it also offers optimum performance characteristics such as smaller settling time and steady state error. Whereas, the control efficiency is demonstrated by Matlab/Simulink simulation to confirm our design parameters.